Breaking the silence: factors influencing complementary therapy disclosure among diabetic outpatients in Taiwan - Hsiao-Yun Chang (BMC Complementary Medicine and Therapies)
Abstract Background As more patients turn to complementary therapies (CTs) alongside conventional medicine, the lack of communication between patients who use CTs and their conventional healthcare professionals (HCPs) can pose significant risks, including the potential for serious drug interactions. Purpose To explore the factors influencing the disclosure of CTs use to conventional HCPs. Methods A cross-sectional survey design was employed to enroll 307 outpatients diagnosed with diabetes from both the northern and southern regions of Taiwan, covering the period from October 2022 to March 2023. The survey questionnaire included demographics, the patterns of CTs use, the experiences of CTs use, the Understanding the Benefit-Risks of CTs Use Scale, and the Diabetes Empowerment Scale. The data were analyzed using IBM SPSS Statistics version 28.0. Results Only one-third of outpatients with diabetes disclosed their use of CTs to conventional HCPs. Several factors emerged as influential in this disclosure: understanding the benefits and risks of CTs use (OR = 1.10), the reasons for initial CTs use (OR = 1.58), integration of both conventional and complementary medicines (OR = 15.03), and the use of manipulative-based therapies (OR = 6.82). Conclusion Understanding the factors that influence the disclosure of CTs use is essential for conventional HCPs. This understanding allows them to identify outpatients who may hesitate to disclose their CTs use and ensures they have a comprehensive understanding of their patients' CTs use, thereby facilitating effective communication.